Parents’ Knowledge and Behavior Related to Pneumonia Incidence in Children Under Five: A Literature Review - Lale Nubya Nitzana; Wayan Sulaksmana Sandhi Parwata; Titi Pambudi Karuniawaty (Jurnal Biologi Tropis, 2026)
Pneumonia remains a leading cause of morbidity and mortality among children under five worldwide, including in Indonesia, with its severity influenced by immunization status, air pollution exposure, delayed access to healthcare, and families’ socioeconomic and behavioral conditions.of families influence the severity of pneumonia. This review aims to explore parental knowledge and behavior and the severity of pneumonia in children under five based on previous studies. This study used a literature review method by collecting and analyzing relevant articles from databases such as PubMed, Google Scholar, and ScienceDirect using keywords including "pneumonia", "knowledge", "behavior", and "under-five children". The findings indicate that adequate parental knowledge about pneumonia can support early detection and timely medical care. Parents with better knowledge tend to recognize the early symptoms of pneumonia more quickly and promptly seek medical care. In addition, good preventive behaviors, such as proper hygiene practices, complete immunization, and adequate care, can help prevent pneumonia or reduce the severity of the disease if it occurs. However, some studies show that high knowledge does not always correlate with appropriate treatment-seeking behavior, as it is influenced by other factors such as education level, economic status, and access to healthcare facilities. In addition, poor preventive behavior such as smoking inside the house and inadequate sanitation contributes to increased risk and severity of pneumonia. Parental knowledge and behavior play a crucial role in the prevention and management of pneumonia in children. However, a holistic approach is required, considering educational, economic, and healthcare access factors to ensure effective interventions in reducing the incidence and severity of pneumonia among children.